MEASURING FIRM VALUES: THE ROLE OF ITS DETERMINING FACTORS - Santoso, Aprih; Sulistyawati, Ardiani Ika; Hapsari, Dian Indriana (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study aims to analyze the effect of profitability on company value with CSR as the moderation and the effect of profitability and GCG on company value and company size on profitability in Registered Food and Beverage Industry Sub-Sector Companies in the 2014 – 2021 period. The population is all Companies in the Food and Beverage Industry Sub-Sector that are Registered on the IDX for the period 2014 - 2021, while the sample was determined using purposive sampling and obtained 35 companies as the research sample. Structural Equation Modeling (SEM) is used as an analysis tool with the Partial Least Square (PLS) program application, namely smartPLS.3.0. The results of hypothesis testing indicate that firm value can be manifested through optimal management of profitability and GCG. Profitability can be applied through the size of the company. GCG has a significant direct effect on company value, while company size has a significant direct effect on profitability. GCG has a significant direct effect on profitability and a significant direct effect on firm value. CSR is able to function as a pure moderator of the influence of profitability on firm value.